Polyinosinic acid is a ligand for toll-like receptor 3. - Marshall-Clarke, S; Downes, J; Haga, I; Bowie, A; Borrow, P; Pennock, J; Grencis, R; Rothwell, P (2007)
Innate immune responses are critical in controlling viral infections. Viral proteins and nucleic acids have been shown to be recognized by pattern recognition receptors of the Toll-like receptor (TLR) family, triggering downstream signaling cascades that lead to cellular activation and cytokine production. Viral DNA is sensed by TLR9, and TLRs 3, 7, and 8 have been implicated in innate responses to RNA viruses by virtue of their ability to sense double-stranded (ds) RNA (TLR3) or single-stranded RNA (murine TLR7 and human TLR8). Viral and synthetic dsRNAs have also been shown to be a potent adjuvant, promoting enhanced adaptive immune responses, and this property is also dependent on their recognition by TLR3. It has recently been shown that mRNA that is largely single-stranded is a ligand for TLR3. Here we have investigated the ability of single-stranded homopolymeric nucleic acids to induce innate responses by murine immune cells. We show for the first time that polyinosinic acid (poly(I)) activates B lymphocytes, dendritic cells, and macrophages and that these responses are dependent on the expression of both TLR3 and the adaptor molecule, Toll/IL-1 receptor domain-containing adaptor inducing IFN-beta (TRIF). We therefore conclude that TLR3 is able to sense both single-stranded RNA and dsRNA.